Clarifying an Image: The “Misrepresentation” of Major John Richardson - Finlayson, Alan (Ontario History, 2024)
Major John Richardson has been recognized as Canada’s first internationally recognized author and the “Father of Canadian Literature” but despite these acknowledgements, has often been portrayed in a negative light as a failure, a novelist who was “unknown” or “ignored” in Canada and who failed as well in the United States where he died in poverty. He has also been portrayed as “a Hotspur,” who constantly “sought” trouble and a mere imitator of James Fenimore Cooper. These depictions misrepresent him and are based on half-truths and assumptions and are in need of clarification.